Ecological aspects of increasing intensity in pepper forcing with prime attention to the type of the growing equipment - Kicska , Tibor (Applied Studies in Agribusiness and Commerce, 2017)
Significant amount of profit can be generated in forcing technologies by the efficient use of different elements in growing technologies, however, improving production intensity is on the agenda in the sector. Pepper forcing, as the most significant class of vegetable forcing, practically takes place under all the growing equipment widespread in our country, but there is a considerable difference in context of profitability and efficiency. This paper wonders whether the most intensive technology in pepper forcing is efficient regarding the use of forcing equipment, namely modern greenhouses, or growing under greenhouses with significantly lower investment cost is more efficient. The analysis represents cost-income factors and efficiency assessed on a long-term basis of different technologies via a deterministic model based on producers’ data collections. As a result of the research, economic indicators are calculated based on exact results which will help to conduct a comparative assessment of economic features in technological varieties. JEL code: Q12